Social Media and Online Communities' Effect on Organic Product Purchase Intention in Emerging Markets - Labiad Samir; Marso Saida (Communications of International Proceedings, 2024)
Customer purchase intention is impacted by various factors and have been studied extensively in literature and invarious contexts. Organic products are becoming more and more popular with many people seeking to live healthier lifestyles whereas social media has also presented customers with a new aesthetic that is pleasing to them and incorporates organic products. Hence, through literature review, this study assessed the influence of social media and online communities on customer purchase intention. The specific objectives of the study were to: Establish the effect of social media platforms on the purchases of organic product in emerging markets; Establish the role of instagrammability on customer purchase intention of organic products; Determine the role of online communities on customer purchase intention of organic products in emerging markets. It is understood that social media does play a part in influencing customer behavior in case of organic products. This is especially notable in emerging markets that is new to the digital world. The availability of knowledge regarding organic products on social media platforms have had a significant impact on purchase intention of consumers as they can see reviews in real time and order based on electronic word of mouth. This study is limited as it only includes studies that have self-reported results of internet users regarding purchase intention towards organic foods.
Keywords: Consumer Behavior; Organic Food; Emerging Markets; Social Media; Online Community